Macroeconomic Determinants of Stock Market Returns in the Gulf Cooperation Council - Alshihab, Salem (International Journal of Economics and Financial Issues, 2021)
This study investigates the impact of certain macroeconomic determinants on stock market returns in the Gulf Cooperation Council (GCC). Those macroeconomic factors are: interest rates, oil prices, exchange rates, and money supply. Those factors were empirically studied and investigated to have an impact on stock market returns in many countries. This paper also attempts to capture that impact of those macroeconomic factors on the stock market, using a panel set of data by implying several tests on the data, which include unit root tests, cointegration test, and error correction model (ECM). The empirical results support previous studies that suggest the high reliance of governments and stock markets in the GCC on macroeconomic determinants, specifically oil prices, while other determinants were found to have less effect on stock market returns than oil prices. The findings of the study will presumably enable investors and stakeholders in making better investment decisions, in addition to assisting policy-makers in enhancing the efficiency of stock markets and better regulating them. Keywords: Stock Market, Oil Prices, Interest Rates, Exchange Rates, Money Supply (M2) JEL Classifications: Q41, E02, G1, N95 DOI: https://doi.org/10.32479/ijefi.11189